Tren dan Tantangan dalam Manajemen Industri Haji dan Umroh: Perspektif Global dan Lokal - Maela Aulia; Yuyun Affandi; Abdul Rozaq (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
In recent years, trends in the management of the Hajj and Umrah industry have experienced significant changes influenced by globalization, technological advances and socio-economic dynamics. The industry has various challenges such as currency exchange rate fluctuations, visa clearances from Saudi Arabian authorities, regulatory changes, and stiff competition among travel agents. This research aims to analyze trends and challenges in the management of the Hajj industry from a local and global perspective to ensure the sustainability and effectiveness of managing this industry in the future. Through qualitative research methods with a literature study approach, the research results show that the management of the Hajj and Umrah industry is experiencing social changes (trends) such as the digitization of services, improving service quality, more varied travel packages, and the involvement of social media as a process for transferring travel agent information. However, behind this positive trend, Hajj industry management faces complex challenges such as policy changes, competition and crime in Hajj and Umrah organizers. To overcome this, agents need to be careful in developing pricing and promotion strategies and always follow the latest developments from the government and related authorities.